Procesos migratorios y su impacto socio cultural en la población de Cayhuayna, Pillco Marca 2013 - Zevallos Fretel, Edwin (2017)
The member accomplished present investigation himself with the principal purpose to know the impact of the migrant processes in aspects cultural of Cayhuayna’s population, having under consideration than of late years, I space this geographic and populated surrounding centers have recepcionado great number of inhabitants of other places. For your execution has used him procedures best- suited metodológicos, such like the documentary analysis and bibliographic envelope the migrant processes and aspects member cultuales; Besides you have applied over himself questionnaires of opinion related to the independent and dependent variable, whose data have allowed us elaborating the statistical pictures for their analysis and interpretation. The results have become concrete in the following premises: To ) The social and cultural reality of Cayhuayna’s population, you have improved of significant way of arrival of different places of the region and the country b to the moments comparatively ) the inhabitants’ migrant processes have changed their event experienceds in life significantly member cultural originals c ) The migrant processes of Cayhuayna’s inhabitants influenced significantly in: The access to the services of internet ( 74 % ); Change of the mode of work ( 77 % ); I change of mode of nutrition ( 74 % ); I change in your dressing mode ( 70 % ), get better in your health ( 63 % ), I change in the mode relation with your social surroundings ( 85 % ), I change in your social standing ( 67 % ), get better in his cost-reducing income ( 81 % ), get better in his basic services ( 77 % ). B ) The migrant processes of Cayhuayna’s inhabitants influenced significantly in the cultural aspect, in the change of their preference referring to the practice of the  dance, the dance and music ( 62 % ); They have changed the practice of his habits in a 53 % in relation to his cultural employers originating.